Tipos de conocimiento para la asociatividad empresarial en las Mipymes del sector metalmecánico de la Región Caribe colombiana (2021)
The analysis focused on the different definitions of business associativity reveals as a result four types of knowledge in the organization: tacit knowledge and explicit knowledge, according to an epistemological conception, and on the other hand, individual knowledge and social or collective knowledge are raised from the ontological point of view. These types of knowledge are fully differentiated in terms of their availability, access and manageability. Some authors such as Davenport and others (2014), argue that in organizations knowledge varies from specialized, complex and accumulated knowledge, which resides in individuals and is largely inexpressible, which is when talking about tacit knowledge, to a much more structured and explicit content. In this sense, the authors differentiate knowledge from the point of view of its technical nature, its complexity and that which has been stored and collected to ensure the efficiency of processes in organizations. This work seeks to identify and describe the different types of knowledge required by MIPYMEs in the metalworking sector of the Colombian Caribbean region to use business associations for administrative processes in them in order to improve their productivity and competitiveness.